The Fight to Capture Light: Functional Diversity Is Related to Aquatic Plant Community Productivity Likely by Enhancing Light Capture - Angove, Charlotte; Norkko, Alf; Gustafsson, Camilla (Frontiers in Marine Science, 2020)
Functional Diversity (FD) experiments are highly effective for investigating how a community interacts with its environment. However, such experiments using morphological and chemical traits have not been conducted for submerged aquatic plants and their insights would be highly valuable for understanding the ecology of these communities. We conducted a 15-week field experiment in the Baltic Sea where we manipulated the species composition of aquatic plant communities to investigate functional diversity. We constructed artificial triculture communities with different species compositions to change the Community Weighted Means (CWMs) and variability of traits. We measured 9 plant traits and tested how community productivity (CP) was related to FD, trait CWMs and community trait ranges. CP varied by more than four times across treatments and functional richness was significantly related to CP. Functional evenness and functional divergence were not significantly related to CP. Height, leaf area and δ¹³C were significantly related to CP. Leaf δ¹³C trends with CP suggested that the carbon supply is not replete, yet species composition was partly responsible for the relationship. Plant height likely had multifaceted benefits to CP because there was evidence of a competitive height interaction between the tallest and 2nd tallest species, therefore the effects of plant height to CP would have been disproportionally large. The height of the tallest species significantly drove the variability of the community height range, which was significantly related to CP and it had a relatively large influence on the calculation of FD indices. Leaf area, which was strongly correlated to plant height, was also significantly related to community productivity. The significant relationship between functional richness and CP was most likely driven by the presence of taller plants. FD likely enhanced CP, by selecting for extreme trait values which enhanced production (selection effect), while niche complementarity effects were not observed. This study provides experimental evidence and mechanistic insights into the role of FD and specific traits for CP in submerged aquatic plant communities. To conclude, FD was significantly related to CP of temperate aquatic plant communities likely by selecting for traits which enhanced light capture, with consequences for carbon supply.